2014
DOI: 10.3389/fpls.2014.00548
|View full text |Cite
|
Sign up to set email alerts
|

From soil to plant, the journey of P through trophic relationships and ectomycorrhizal association

Abstract: Phosphorus (P) is essential for plant growth and productivity. It is one of the most limiting macronutrients in soil because it is mainly present as unavailable, bound P whereas plants can only use unbound, inorganic phosphate (Pi), which is found in very low concentrations in soil solution. Some ectomycorrhizal fungi are able to release organic compounds (organic anions or phosphatases) to mobilize unavailable P. Recent studies suggest that bacteria play a major role in the mineralization of nutrients such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 89 publications
(120 reference statements)
0
75
0
Order By: Relevance
“…Soil microbial biomass P (SMBP) is one of the major biological sinks: P held in microbial biomass acts as a labile pool, which prevents fixation and becomes available for plant capture during microbial turnover (Becquer et al 2014). The impact of the interaction between earthworms and AM fungi on microbial biomass P was significantly marked (Table 2), which indicated that earthworms and AM fungi had a positive interaction on microbial turnover in the P cycling.…”
Section: Microbial Biomass P With P Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil microbial biomass P (SMBP) is one of the major biological sinks: P held in microbial biomass acts as a labile pool, which prevents fixation and becomes available for plant capture during microbial turnover (Becquer et al 2014). The impact of the interaction between earthworms and AM fungi on microbial biomass P was significantly marked (Table 2), which indicated that earthworms and AM fungi had a positive interaction on microbial turnover in the P cycling.…”
Section: Microbial Biomass P With P Cyclingmentioning
confidence: 99%
“…The shortage of available P in soils is one of the key chemical factors limiting plant growth because P is one of the most limiting macronutrients in soil (Becquer et al 2014). To increase agricultural production, large amounts of soluble-P fertilizers are widely applied, and plants take up P from soil predominantly in its mineral form and H 2 PO 4 − ) determined by the soil pH (Bucher 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Becquer et al (2014) described the journey of P from the soil to the plant through trophic relationships and ectomycorrhizal association to understand the ecological and molecular mechanisms responsible for transferring Pi and improving plant P nutrition. Ectomycorrhizal fungi improve nutrient status of plants, as they are able to release organic anions or phosphatases to mobilize unavailable P (Louche et al 2010;Plassard and Dell 2010).…”
Section: Phosphorus (P)mentioning
confidence: 99%
“…Furthermore, bacteria play a major role in the mineralization of P through trophic relationships as they can produce phytases to degrade phytate, the main form of soil organic P. Bacteria are also more effective than other microorganisms or plants at immobilizing free Pi. Interestingly, free Pi may be taken up by ectomycorrhizal fungi by specific phosphate transporters and transferred to the plant by mechanisms not yet been identified (Becquer et al 2014).…”
Section: Phosphorus (P)mentioning
confidence: 99%
“…Outside the mantle, the extraradical mycelium forms an extensive network in the soil and can represent 75 % of the potential absorbing system area and over 99 % of the nutrient-absorbing length in pine roots (Rousseau et al 1994). Ectomycorrhizae are particularly important in N uptake and also make a significant contribution to P nutrition (Jones et al 1998;Bücking et al 2012;Becquer et al 2014). …”
mentioning
confidence: 99%